A+ guide to hardware - Andrews, Jean (Thomson/Course Technology, 2006)
Step-by-step resource for learning the fundamentals of supporting and troubleshooting computer hardware. It also maps fully to CompTIA's A+ 2003 Upgrade Core Hardware Exam. For undergraduate students